Functionalized fabric

By using functionalized fabrics containing a small amount of high-efficiency adhesives in the production of wind turbine blades, the problems of low production efficiency and mechanical characteristics in the prior art are solved, and efficient and excellent wind turbine blades are achieved. Production.

CN119173365APending Publication Date: 2024-12-20OWENS CORNING INTELLECTUAL CAPITAL LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039031.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2023-03-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is inefficient in the production of reinforced structural components of wind turbine blades, and excessive use of adhesives affects mechanical properties.

Method used

Functionalized fabrics containing small amounts of binder particles with a glass transition temperature not exceeding 75°C, the binder accounts for no more than 5% of the total weight, and a fabric stack is formed by heating to improve production efficiency.

Benefits of technology

The production speed and mechanical characteristics of wind turbine blades are significantly improved without affecting the performance of the final components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173365A_ABST
    Figure CN119173365A_ABST
Patent Text Reader

Abstract

Described herein is a functionalized fabric comprising a fibrous fabric and a binder having a glass transition temperature of about 75 DEG C or less wherein the binder comprises up to about 5% by weight of the functionalized fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to functionalized fabrics comprising glass fibers and / or carbon fibers, in particular functionalized fabrics for reinforcing structural components, such as wind turbine components. Background Art

[0002] It is well known that glass fibers and / or carbon fibers may be used to form reinforcing fiber fabrics to reinforce structural components such as wind turbine blades or related components (eg, spar caps).

[0003] Structural components comprising reinforcing fiber fabric (reinforced structural components) are typically formed by stacking layers of reinforcing fiber fabric in a mold, filling the mold with resin, and curing the resin to form the component. This process can be time consuming.

[0004] As the search for alternative energy sources continues, the use of wind energy and wind turbines has received increasing attention. As interest in harnessing wind energy to generate more energy has grown, technological advances in the field have allowed for increased sizes of wind turbine blades. Increasing the size of wind turbine blades has also increased the time required to produce wind turbine blades.

[0005] It would be desirable to provide improvements in enhancing the efficiency of the production of structural components, such as wind turbine blades. Summary of the invention

[0006] Most generally, the present invention provides a functionalized fabric comprising a fibrous fabric and a binder having a glass transition temperature of up to about 75° C., the binder comprising up to about 5% by weight of the functionalized fabric.

[0007] In one aspect, the present invention provides a functionalized fabric comprising:

[0008] Fabrics; and

[0009] Binder particles having a glass transition temperature of at most about 75°C,

[0010] The fiber fabrics include:

[0011] first fibers oriented in a first direction; and

[0012] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0013] wherein the binder particles comprise up to about 5 wt % (e.g., about 0.1 wt % to about 3.5 wt %) of the functionalized fabric, and optionally, the functionalized fabric comprises about 2 g / m 2 About 20g / m2 of binder particles.

[0014] In one aspect, the present invention provides a functionalized fabric comprising:

[0015] Fabrics; and

[0016] Binder particles having a glass transition temperature of at most about 75°C,

[0017] The fiber fabrics include:

[0018] first fibers oriented in a first direction; and

[0019] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0020] wherein the binder particles comprise up to about 5 wt % (e.g., about 0.1 wt % to about 3.5 wt %) of the functionalized fabric, the binder particles being adhered to the surface of the fibrous fabric, and optionally, the functionalized fabric comprising about 2 g / m 2 About 20g / m 2 of binder particles.

[0021] In one aspect, the present invention provides a functionalized fabric comprising:

[0022] Fabrics; and

[0023] A binder having a glass transition temperature of at most about 75°C,

[0024] The fiber fabric comprises: first fibers oriented along a first direction; and second fibers oriented along a second direction, wherein the first fibers include glass fibers and / or carbon fibers, the second fibers include glass fibers and / or carbon fibers, and the second direction is within 0 to 90 degrees of the first direction,

[0025] wherein the binder comprises up to about 5% by weight of the functionalized fabric, and

[0026] The functionalized fabric has a surface having at least some binder present thereon, the surface having an average gloss value of about 65 G.U. or less.

[0027] In one aspect, the present invention provides a fabric laminate comprising at least two functionalized fabric layers as described herein.

[0028] In one aspect, the present invention provides a shaped part comprising a fabric laminate as described herein.

[0029] In one aspect, the present invention provides a method for producing a functionalized fabric, the method comprising:

[0030] Providing a fiber fabric, the fiber fabric comprising first fibers oriented in a first direction and second fibers oriented in a second direction, the first fibers comprising glass fibers and / or carbon fibers, the second fibers comprising glass fibers and / or carbon fibers, and the second direction being within 0 to 90 degrees of the first direction;

[0031] applying binder particles having a glass transition temperature of up to about 75° C. to the fiber fabric; and adhering the binder particles to the fiber fabric to provide a functionalized fabric, wherein the binder is applied to the fiber fabric in an amount such that the binder comprises up to about 5% by weight of the functionalized fabric.

[0032] In one aspect, the present invention provides a method for producing a functionalized fabric, the method comprising:

[0033] Providing a fiber fabric, the fiber fabric comprising first fibers oriented in a first direction and second fibers oriented in a second direction, the first fibers comprising glass fibers and / or carbon fibers, the second fibers comprising glass fibers and / or carbon fibers, and the second direction being within 0 to 90 degrees of the first direction;

[0034] applying a binder having a glass transition temperature of up to about 75° C. to the fiber fabric to provide a functionalized fabric; and

[0035] Adhere the adhesive to the fabric,

[0036] wherein the binder is applied to the fiber fabric in an amount such that the binder comprises up to about 5% by weight of the functionalized fabric, and

[0037] Wherein the functionalized fabric has a surface having at least some binder present thereon, the surface having an average gloss value of about 65 G.U. or less.

[0038] In one aspect, the present invention provides a method for producing a shaped part, the method comprising:

[0039] stacking a plurality of functionalized fabric layers described herein;

[0040] shaping the stacked plurality of fabric layers to form a shaped stack;

[0041] The shaped layup is heated at a temperature up to about 150°C to provide a shaped part.

[0042] In one aspect, the present invention provides a roll of a functionalized fabric as described herein.

[0043] The present inventors have discovered that the present invention provides a functionalized fabric that offers improvements in the production efficiency of reinforced structural components such as wind turbine blades and related components.

[0044] The present inventors have discovered that attaching a small amount of binder particles to a fibrous fabric as described herein (e.g., less than 5 wt % (e.g., less than 3.5 wt % or 0.1 wt % to 3.5 wt %) and / or about 2 g / m 2 About 30g / m 2 (For example, about 2 g / m 2 About 20g / m 2 ) provides a functionalized fabric having independent binder particles (e.g., adhered binder particles having a maximum axial length of up to about 1 mm) adhered to the surface of the fiber fabric, and the resulting functionalized fabric has excellent processability and provides improvements in the efficiency of the production of reinforced structural components (such as wind turbine blades).

[0045] The present inventors have discovered that the functionalized fabrics described herein can be stacked to form a fabric stack, and the binder of the functionalized fabric allows the fabric layers of the fabric stack to adhere to each other to form a consolidated fabric stack that exhibits excellent adhesion. The present inventors have also discovered that the functionalized fabrics, fabric stacks, and consolidated fabric stacks described herein can be directly shaped, and once shaped, the shaped fabric or fabric stack retains the shaped form (e.g., after being removed from the mold).

[0046] The present inventors have surprisingly found that a small amount of a binder (e.g., binder particles) as described herein (e.g., less than 5 wt % (e.g., less than 3.5 wt % or 0.1 wt % to 3.5 wt %) and / or about 2 g / m 2 of the functionalized fabric having a glass transition temperature of up to about 75° C. 2 About 30g / m 2 (e.g. about 2 g / m 2 About 20g / m 2 ) functionalized fabric) and a functionalized fabric having a surface with an average gloss value of about 65 G.U. or less (e.g., about 25 G.U. to about 65 G.U. or about 25 G.U. to about 65 G.U.) can be stacked and formed (i.e., preformed) prior to being incorporated into a reinforced structural component.

[0047] It has been found that the provision of the functionalized fabrics described herein surprisingly increases the speed at which reinforced structural parts (e.g., wind turbine blades) can be produced. It has also been found that the functionalized fabrics described herein exhibit excellent handleability, in particular the functionalized fabrics can be rolled, cut, and stacked without shedding binder. Even more surprisingly, the inventors have found that the functionalized fabrics described herein can provide improvements in the efficiency of production of reinforced structural parts (e.g., wind turbine blades) without adversely affecting the mechanical properties of the fabric or the final part.

[0048] The present invention includes any combination of aspects, embodiments and preferred features described herein except where such a combination is expressly impermissible or expressly avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Embodiments and experiments illustrating the principles of the present invention will now be discussed with reference to the accompanying drawings, in which:

[0050] Figure 1 is a graph showing the particle size distribution of various binder particles that may be applied to a fiber fabric to produce a functionalized fabric as described herein;

[0051] Figure 2 is an image of the functionalized fabric described in this article generated by 3D microscopy;

[0052] Figure 3a is a schematic diagram of a cross section of a fabric laminate;

[0053] Figure 3b is a schematic diagram of a cross section of a fabric laminate;

[0054] Figure 4a is an image of the functionalized fabric described in this article generated by 3D microscopy;

[0055] Figure 4b It is shown Figure 4a A graph of the binder particle size distribution on the surface of the functionalized fabric shown;

[0056] Figure 5a is an image of the functionalized fabric described herein produced by a 3D microscope; and

[0057] Figure 5b It is shown Figure 5b A graph showing the binder particle size distribution on the surface of the functionalized fabric is shown. DETAILED DESCRIPTION

[0058] Various aspects and embodiments of the present invention will now be discussed with reference to the accompanying drawings. Additional aspects and embodiments will be apparent to those skilled in the art.

[0059] Described herein is a functionalized fabric comprising a fibrous fabric and binder particles adhered to a surface of the fibrous fabric and having a glass transition temperature of about 75° C. or less, the binder particles comprising up to about 5% by weight of the functionalized fabric.

[0060] Also described herein is a functionalized fabric comprising a fibrous fabric and a binder (e.g., binder particles), the binder having a glass transition temperature of about 75°C or less and accounting for up to about 5% by weight of the functionalized fabric, the functionalized fabric having a surface comprising the binder, the surface having an average gloss value of about 65 G.U or less.

[0061] Fiber fabric

[0062] The fabric contains:

[0063] first fibers oriented in a first direction; and

[0064] second fibers oriented in a second direction,

[0065] The first fibers include glass fibers and / or carbon fibers, the second fibers include glass fibers and / or carbon fibers, and the second direction is within 0 to 90 degrees of the first direction.

[0066] The first fibers of the fiber fabric may be referred to as warp fibers. The first fibers may be arranged side by side and substantially parallel to each other. The second fibers of the fiber fabric may be referred to as weft fibers. The second fibers may be arranged side by side and substantially parallel to each other.

[0067] In an embodiment, the fiber fabric comprises first fibers oriented in a first direction and second fibers oriented in a second direction, wherein the second direction is within 0 to 90 degrees of the first direction, for example, within about 10 to about 90 degrees of the first direction, within about 20 to about 90 degrees of the first direction, within about 30 to about 90 degrees of the first direction, within about 40 to about 90 degrees of the first direction, within about 45 to about 90 degrees of the first direction, within about 60 to about 90 degrees of the first direction, within about 70 to about 90 degrees of the first direction, within about 80 to about 90 degrees of the first direction, within about 85 to about 90 degrees of the first direction, within about 88 to about 90 degrees of the first direction, or within about 90 degrees of the first direction.

[0068] In an embodiment, the fiber fabric may be a unidirectional fabric or a multi-axial fabric, such as a bi-axial fabric.

[0069] In an embodiment, the fiber fabric is a unidirectional fabric. The fiber fabric for a unidirectional fabric may include a second fiber oriented in a second direction, wherein the second direction is oriented in a direction greater than 0 degrees in the first direction. For example, the unidirectional fabric may include a first fiber oriented in a first direction and a second fiber oriented in a second direction, wherein the second direction is about 0 degrees to 90 degrees of the first direction, for example, within about 45 degrees to about 90 degrees of the first direction, within about 60 degrees to about 90 degrees of the first direction, within about 70 degrees to about 90 degrees of the first direction, within about 80 degrees to about 90 degrees of the first direction, within about 85 degrees to about 90 degrees of the first direction, within about 88 degrees to about 90 degrees of the first direction, or within about 90 degrees of the first direction. In a unidirectional fabric, the first fiber may account for more than about 90 weight % of the fiber fabric, for example, more than about 92 weight % of the fiber fabric, or at least about 95 weight % of the fiber fabric. In a unidirectional fabric, the second fiber may account for at most about 10 weight % of the fiber fabric, for example, at most about 8 weight %, or at most about 5 weight %. In a unidirectional fabric, the second direction may be substantially perpendicular to the first direction, the first fibers may comprise greater than 92% by weight of the fiber fabric, and the second fibers may comprise up to about 8% by weight of the fiber fabric. In an embodiment, the fiber fabric is a unidirectional fabric, the second direction is substantially perpendicular to the first direction, and the weight ratio of the first fibers to the second fibers is in the range of 15:1 to 25:1.

[0070] In an embodiment, the fiber fabric is a biaxial fabric. In a biaxial fabric, the second direction may be within about 20 degrees to about 90 degrees of the first direction, for example, the second direction may be within about 30 degrees to about 90 degrees of the first direction, the second direction may be within about 40 degrees to about 90 degrees of the first direction, the second direction may be within about 45 degrees to about 90 degrees of the first direction, the second direction may be within about 60 degrees to about 90 degrees of the first direction, within about 70 degrees to about 90 degrees of the first direction, within about 80 degrees to about 90 degrees of the first direction, within about 85 degrees to about 90 degrees of the first direction, within about 88 degrees to about 90 degrees of the first direction, or within about 90 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, wherein the second direction is about 25 degrees to 75 degrees of the first direction, for example, about 45 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, wherein the second direction is at least 45 degrees of the first direction. In an embodiment, the fiber fabric is a biaxial fabric, and the second direction is substantially perpendicular to the first direction. In embodiments where the fiber fabric is a biaxial fabric, the second fibers comprise greater than 5% by weight of the fiber fabric. In embodiments where the fiber fabric is a biaxial fabric, the second fibers may comprise at least about 10% by weight of the fiber fabric, such as at least about 15% by weight, at least about 20% by weight, or at least about 25% by weight of the fiber fabric.

[0071] In embodiments, at least the first fibers or the second fibers comprise, consist essentially of, or consist of glass fibers.

[0072] In embodiments, the first fibers and the second fibers both comprise, consist essentially of, or consist of glass fibers.

[0073] In embodiments, the glass fibers comprise at least about 50% by weight of the fiber fabrics described herein, e.g., at least about 60% by weight of the fiber fabric, at least about 70% by weight of the fiber fabric, at least about 80% by weight of the fiber fabric, at least about 90% by weight of the fiber fabric, or at least about 95% by weight of the fiber fabric.

[0074] The term "glass fiber" is used herein to refer to a plurality of continuous glass filaments (the term "continuous" as used herein is used to refer to fibers / filaments having a length that is many times its diameter, such as at least about 5000 times its diameter, such as at least about 10,000 times its diameter). The glass fibers used in the fabrics described herein can be provided as glass fiber strands (or bundles). The glass fibers can be formed by a continuous manufacturing process in which molten glass passes through the holes of a "buffer plate" and the molten glass stream formed thereby solidifies into filaments / fibers. The glass fibers described herein (e.g., the glass fibers of the first fibers and / or the second fibers) can include a sizing agent on their surface, such as a sizing agent applied to the glass fibers during fiber formation. The sizing agent can include components that promote the formation of the glass fibers and / or their use in the matrix resin, such as a film former, a lubricant, a coupling agent (to promote compatibility between the glass fibers and the resin used to form the composite product containing the hybrid fabric described herein), etc. In some embodiments, the glass fibers of the first fibers and / or the second fibers include a polyester compatible sizing or an epoxy compatible sizing.

[0075] As used herein, the term "glass fiber strand" or "glass fiber tow" refers to a bundle of continuous glass filaments. In an embodiment, the glass fiber strand or tow is a plurality of bundles of untwisted glass filaments.

[0076] In an embodiment, the glass fiber strands or glass fiber bundles are provided by glass fiber direct rovings. Glass fiber direct rovings consist of a bundle of continuous untwisted (ie, substantially parallel or parallel) glass filaments bonded (when forming glass filaments) into a single strand and wound onto a bobbin.

[0077] Any suitable glass reinforcing fiber may be used as the first fiber or the second fiber. For example, E glass, E-CR glass (such as Advantex available from Owens Corning) may be used. TM Glass fibers), fibers made of C-glass, H-glass, S-glass, and AR glass types.

[0078] In an embodiment, the linear mass density of the glass fibers referred to herein (e.g., the first fibers that may be glass fibers and / or the second fibers that may be glass fibers) ranges from about 50 tex to about 5000 tex, for example, from about 200 tex to about 4800 tex, from about 300 tex to about 2500 tex, from about 300 tex to about 2400 tex, or from about 600 tex to about 1200 tex.

[0079] The term "carbon fiber" is used herein to refer to a plurality of continuous carbon filaments (the term "continuous" as used herein is used to refer to a fiber / filament having a length that is many times its diameter, such as at least about 5000 times its diameter, such as at least about 10 000 times its diameter). The carbon fibers used in the fabrics described herein can be provided as carbon fiber tows (or strands), which are bundles of continuous carbon filaments. The carbon fibers described herein (e.g., the carbon fibers of the first fibers and / or the second fibers) may include a sizing agent on their surfaces, such as a sizing agent applied to the carbon fibers during fiber formation. The sizing agent may include components that promote the formation of carbon fibers and / or their use in a matrix resin, such as a film former, a lubricant, a coupling agent (to promote compatibility between carbon fibers and a resin for forming a composite product comprising a hybrid fabric described herein), etc. In some embodiments, the carbon fibers include a polyester compatible sizing agent or an epoxy compatible sizing agent.

[0080] In an embodiment, the linear mass density of the carbon fibers ranges from about 100 tex to about 5000 tex, e.g., from about 200 tex to about 5000 tex, from about 400 tex to about 5000 tex, from about 600 tex to about 5000 tex, from about 800 tex to about 5000 tex, from about 100 tex to about 4800 tex, from about 200 tex to about 4800 tex, from 400 tex to about 4800 tex, from about 600 tex to about 4800 tex, 00 tex, about 800 tex to about 4800 tex, about 100 tex to about 2400 tex, about 200 tex to about 2400 tex, about 400 tex to about 2400 tex, about 100 tex to about 2000 tex, about 200 tex to about 2000 tex, about 400 tex to about 2000 tex, about 600 tex to about 2000 tex, about 800 tex to about 2000 tex, or about 1200 tex.

[0081] In an embodiment, the carbon fiber (when present) is provided by a carbon fiber tow (carbon fiber strand). In an embodiment, the size of the carbon fiber tow ranges from 6K to 50K, such as 6K to 24K or 6K to 12K. For example, the first fiber can be fed from one or more carbon fiber tows ranging in size from 6K to 50K, such as 6K to 24K or 6K to 12K. The designation #K means that the carbon tow consists of #×1,000 individual carbon filaments, i.e., a carbon fiber tow of size 6K consists of approximately 6000 carbon fiber filaments / fibers.

[0082] In an embodiment, the fabric is a non-crimped fabric, and the first fiber and the second fiber utilize stitching yarn to remain on their corresponding orientation (rather than the first fiber and the second fiber are woven together, i.e., the non-crimped fabric is a non-woven fabric). Any suitable stitching yarn can be adopted. In an embodiment, the stitching yarn is a polyester yarn. In an embodiment, the linear mass density range of the stitching yarn is from about 50 dtex to about 300 dtex. In an embodiment, the stitching yarn passes through fabric to form a stitching pattern, and this stitching pattern can be selected from tricot stitching pattern, symmetrical double tricot stitching pattern, asymmetrical double tricot stitching pattern, symmetrical stitching pattern and asymmetrical stitching pattern. In an embodiment, the stitching yarn passes through fabric to form a stitching pattern, and this stitching pattern is a tricot stitching pattern. In an embodiment, the stitching yarn limits a stitching length, and the scope of this stitching length is from about 2mm to about 7mm, for example, about 3mm.

[0083] In an embodiment, the fiber fabric is a woven fabric, such as a plain woven fabric, a warp knit fabric, or a twill woven fabric.

[0084] In an embodiment, the fiber fabric consists essentially of or consists of glass fibers and / or carbon fibers. In an embodiment, the fiber fabric consists essentially of or consists of glass fibers and carbon fibers. In an embodiment, the fiber fabric consists essentially of or consists of glass fibers.

[0085] In an embodiment, the fiber fabric comprises glass fibers. In an embodiment, the fiber fabric comprises additional fibers in addition to the glass fibers. In an embodiment, the fiber fabric comprises additional fibers in addition to the glass fibers and / or carbon fibers. Examples of other fibers that may be included in the fiber fabric include polymer fibers, such as PET.

[0086] In an embodiment, the fiber fabric has a weight per unit area in the range of about 200 g / m 2 About 2500g / m 2 , for example about 300g / m 2 About 2000g / m 2 , for example, about 500 g / m 2About 1500g / m 2 , for example, about 500 g / m 2 About 1300g / m 2 , for example, about 1300 g / m 2 About 2500g / m 2 The weight per unit area of ​​a fabric can be determined according to ISO 3374.

[0087] In an embodiment, the fiber fabric comprises:

[0088] first fibers oriented in a first direction; and

[0089] second fibers oriented in a second direction,

[0090] Wherein the first fibers comprise glass fibers, the second fibers comprise glass fibers, the second direction is within 45 degrees to 90 degrees of the first direction, and the first fibers and the second fibers are maintained in their respective orientations by the stitching yarn.

[0091] In an embodiment, the fiber fabric comprises:

[0092] first fibers oriented in a first direction; and

[0093] second fibers oriented in a second direction,

[0094] The first fibers include glass fibers, the second fibers include glass fibers, the second direction is within 45 to 90 degrees of the first direction, the first fibers and the second fibers are maintained in their respective orientations by stitching yarns, and the glass fibers of the first fibers and / or the second fibers contain a polyester compatible sizing agent or an epoxy resin compatible sizing agent.

[0095] In an embodiment, the fiber fabric comprises:

[0096] first fibers oriented in a first direction; and

[0097] second fibers oriented in a second direction,

[0098] The first fibers include glass fibers, the second fibers include glass fibers, the second direction is within 45 degrees to 90 degrees of the first direction, the first fibers and the second fibers are maintained in their respective orientations by stitching yarns, the glass fibers of the first fibers and / or the second fibers contain a polyester compatible sizing agent or an epoxy resin compatible sizing agent, and the fiber fabric has a weight per unit area in the range of about 500 g / m 2 About 2500g / m 2 .

[0099] Binder

[0100] Functionalized fabrics include a binder (e.g., binder particles). Functionalized fabrics may be described herein as including binder particles. Functionalized fabrics may be described herein as including a fiber fabric having binder particles adhered to a surface of the fiber fabric.

[0101] In an embodiment, the binder (e.g., binder particles) includes a resin binder, is substantially composed of a resin binder, or is composed of a resin binder. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin, and the thermoplastic resin is selected from epoxy resins, acrylate resins, or polyester resins. In an embodiment, the binder (e.g., binder particles) includes a thermoplastic resin or is composed of a thermoplastic resin, and the thermoplastic resin is selected from epoxy resins or polyester resins. In an embodiment, the binder includes a resin containing epoxy, acrylate, or ester functional groups or is composed of the resin, such as a resin containing epoxy or ester functional groups. In an embodiment, the binder (e.g., binder particles) includes a bio-based resin or is composed of a bio-based resin, such as a bio-based resin containing epoxy, acrylate, or ester functional groups, such as a bio-based resin containing epoxy or ester functional groups.

[0102] In an embodiment, the glass transition temperature of the binder (e.g., binder particles) is at most about 75°C, such as at most about 70°C, at most about 65°C, at most about 60°C, or at most about 55°C. In an embodiment, the glass transition temperature of the binder is at least about 30°C, such as at least about 35°C or at least about 40°C. In an embodiment, the binder has a glass transition temperature in the range of about 30°C to about 75°C, such as about 40°C to about 70°C. The glass transition temperature of the binder can be determined using differential scanning calorimetry (DSC) according to EN ISO 11357-2 (determination of glass transition temperature). The glass transition temperature of the binder can be determined using differential scanning calorimetry (DSC) according to EN ISO11357-2 (determination of glass transition temperature), wherein the glass transition temperature is determined as the value provided by the second heating cycle. The glass transition temperature of the binder can be determined according to the EN ISO 11357-2 test method by heating the binder at a heating rate of 10K / min at an air flow rate of 80mL / min, from -60°C to 120°C. In an embodiment, the glass transition temperature of the binder can be determined according to the EN ISO 11357-2 test method by heating the binder at a heating rate of 10K / min at an air flow rate of 80mL / min, from -60°C to 120°C, then holding at 120°C for 5 minutes, then cooling from 120°C to -60°C at a cooling rate of 10K / min, then holding at -60°C for 5 minutes, then heating again from -60°C to 120°C at a heating rate of 10K / min, and the glass transition temperature is determined as the value provided by the second heating cycle.

[0103] In an embodiment, the binder (e.g., binder particles) has a melting point such that the binder is completely melted when exposed to a temperature of at most about 120°C for at least a suitable period of time, such as when exposed to a temperature of at most about 110°C for at least a suitable period of time, when exposed to a temperature of at most about 100°C for at least a suitable period of time, or when exposed to a temperature of at most about 90°C for at least a suitable period of time. In an embodiment, the binder has a melting point such that the binder is completely melted when exposed to a temperature ranging from about 60°C to about 120°C, such as from about 80°C to about 120°C for at least a suitable period of time. A suitable period of time may be at most 1 hour, such as at most 30 minutes. A suitable period of time may be at least about 1 minute, such as at least about 5 minutes or at least about 10 minutes.

[0104] In an embodiment, the softening temperature of the binder (e.g., binder particles) ranges from about 50° C. to about 100° C., such as about 60° C. to about 100° C. In an embodiment, the softening temperature can be measured with a binder sample having a thickness of 400 μm and a diameter of 25 mm, using an oscillatory rheometer at 0.1% deformation in a plane-plane geometry, a frequency of 1 Hz, using a heating-cooling-heating cycle, the cycle heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C. The softening temperature is measured during the first heating.

[0105] In an embodiment, the binder is applied to the fiber fabric as binder particles. Before being applied to the fiber fabric, the volume average particle size of the binder particles may be at most about 1 mm, for example, at most about 800 μm, at most about 600 μm, at most about 500 μm, at most about 400 μm, at most about 300 μm, or at most about 200 μm. In an embodiment, before being applied to the fiber fabric, the volume average particle size of the binder particles is greater than about 10 μm, for example, greater than about 20 μm, greater than about 30 μm, greater than about 40 μm, or greater than about 50 μm. In an embodiment, before being applied to the fiber fabric, the volume average particle size of the binder particles ranges from about 10 μm to about 1 mm, for example, from about 20 μm to about 600 μm, from about 30 μm to about 500 μm, from about 40 μm to about 400 μm, or from about 50 μm to about 300 μm. Dynamic light scattering techniques can be used on a dispersion of binder particles to determine the volume average particle size of the binder particles prior to application to the fiber fabric. A particle size analyzer (such as available from Beckman YM The volume average particle size is determined by laser diffraction (i.e., using dynamic light scattering technology on a dispersion of binder particles before application to the fiber fabric) in accordance with ISO13320 2009. After the sample is dispersed in air, it can be analyzed twice as is, and the sample amount for each test is usually about 20g.

[0106] In embodiments, the binder of the functionalized fabric may be described as binder particles.

[0107] The binder particles applied to the fabric can adhere to the surface of the fabric so that the functionalized fabric includes the binder particles adhered to the surface. The binder particles applied to the fabric surface can adhere to the fabric to form the functionalized fabric. Due to the less amount of binder particles applied to the fabric as described herein, the functionalized fabric includes a fabric with the binder particles adhered to the fabric, and the binder particles form independent binder particles on the surface of the fabric (for example, rather than the binder condensing on the surface of the fabric to form a bulk or layer). The terms "independent binder particles" and "discrete binder particles" are used herein to refer to the binder particles adhered to the fabric surface spaced apart from each other, i.e., there is a fabric surface area without binder particles around each binder particle. In an embodiment, the longest axial length of the binder particles adhered to the fabric surface is less than about 2mm, for example, less than about 1mm.

[0108] In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles attached to the fiber fabric surface have a longest axial length of less than about 2 mm, such as less than about 1 mm, less than about 800 μm, less than about 700 μm, less than about 600 μm, or less than about 500 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that the longest axial length of the binder particles attached to the fiber fabric surface is at least about 1 μm, at least about 10 μm, or at least about 20 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles attached to the fiber fabric surface have a longest axial length of at least about 1 μm, at least about 10 μm, or at least about 20 μm.

[0109] In embodiments, the binder particles attached to the functionalized fabric surface have a size distribution such that the longest axial length of the binder particles attached to the fiber fabric surface is in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm.

[0110] In an embodiment, the binder particles adhered to the surface of the functionalized fabric have a particle size distribution such that at least about 90% by weight of the binder particles adhered to the surface of the fiber fabric have a longest axial length in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm, about 10 μm to about 600 μm, or about 10 μm to about 500 μm.

[0111] In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length of less than about 2 mm, such as less than about 1 mm, less than about 800 μm, less than about 700 μm, less than about 600 μm, or less than about 500 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length of at least about 1 μm, at least about 10 μm, or at least about 20 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm, about 10 μm to about 600 μm, or about 10 μm to about 500 μm.

[0112] The longest axial length of the binder particles of the functionalized fabric can be determined by measuring the maximum lateral dimension of the binder particles adhered to the fiber fabric. An optical microscope (such as Keyence YM An optical microscope (such as Keyence TM Optical microscope, such as Keyence YM VHX-500) and associated image analysis software (e.g., ImageJ software) to determine the binder particle size distribution. An optical microscope and associated image analysis software (e.g., as described herein) can be used to calculate the particle size distribution of a given functionalized fabric area (e.g., about 5 mm 2 To about 50mm 2 The functionalized fabric area is within the range of about 5 mm 2 To about 20mm 2 Functionalized fabric area within the range of about 5mm 2 To about 10mm 2 The binder particle size distribution can be determined by measuring the binder particle size distribution on the functionalized fabric area within a range of 5 mm. In an embodiment, an optical microscope and related image analysis software (e.g., as described herein) can be used to calculate the 5 mm 2 or 10mm 2 The binder particle size distribution over the functionalized fabric area is determined.

[0113] In embodiments, the binder of the functionalized fabric can be described as binder particles having a shape that can be detected using a numerical aperture microscope (e.g., Keyence YMVHX-500) and associated image analysis software to determine the volume average particle size (i.e., after application and adhesion / fixation (e.g., by melting) to the fiber fabric) (e.g., the particle size of each particle can be determined as the largest transverse dimension of the particle, i.e., the longest axial length of the particle adhered to the fabric surface). In an embodiment, after application and adhesion / fixation to the fiber fabric, the volume average particle size of the binder particles ranges from about 10 μm to about 1 mm, such as from about 20 μm to about 600 μm, from about 30 μm to about 500 μm.

[0114] In an embodiment, the binder of the functionalized fabric can be described as binder particles, and before being applied to the fiber fabric, the binder particles have a D90 particle size of less than (i.e., 90% by volume of the particles have a particle size less than) about 1 mm, such as less than about 800 μm, less than about 600 μm, less than about 500 μm, less than about 400 μm, less than about 300 μm, or less than about 200 μm. The D90 particle size (by volume) can be determined by sieve analysis according to ISO 8130-1.

[0115] In an embodiment, the shear modulus G of the binder (e.g., binder particles) at 30° C. ranges from about 5 MPa to about 50 MPa, such as from about 5 MPa to about 40 MPa, or from about 7 MPa to about 30 MPa. The shear modulus G of the binder at 30° C. can be measured using an oscillatory rheometer at a frequency of 1 Hz and 0.1% deformation in a plane-plane geometry with a heating-cooling-heating cycle of heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C.

[0116] In an embodiment, the dynamic viscosity η of the binder (e.g., binder particles) at 130° C. ranges from about 1 Pa.s to about 400 Pa.s, such as from about 10 Pa.s to about 400 Pa.s. The dynamic viscosity η of the binder at 130° C. can be measured using an oscillatory rheometer at a frequency of 1 Hz and 0.1% deformation in a plane-plane geometry with a heating-cooling-heating cycle of heating from 30° C. to 130° C. at a rate of 3° C. / min, cooling from 130° C. to 30° C. at a rate of 3° C. / min, and heating from 30° C. to 130° C. from 30° C. to 130° C.

[0117] In an embodiment, the binder (e.g., binder particles) comprises or is composed of a resin containing an epoxy functional group, for example, the binder may be an epoxy resin. In an embodiment, the binder comprises or is composed of an epoxy resin, the molecular weight Mw of which ranges from about 2000 to about 6000, for example, from about 3000 to about 6000, from about 4000 to about 6000, or from about 4500 to about 5500. In an embodiment, the binder comprises or is composed of an epoxy resin, the molecular weight Mw of which ranges from about 2000 to about 6000, and the polydispersity ranges from 1 to 5, for example, from 2 to 4, from 2 to 3, or from 2.5 to 3 (wherein the polydispersity is calculated by Mw / Mn). In an embodiment, the binder comprises or is composed of an epoxy resin, and the epoxy resin is epoxidized BPA or epoxy phenolic resin. In an embodiment, the binder comprises or is composed of an epoxy resin, and the epoxy resin is epoxidized BPA.

[0118] In an embodiment, the binder (e.g., binder particles) comprises a resin containing an ester functional group or is composed of the resin, for example, the binder can be a polyester resin. In an embodiment, the binder comprises a polyester resin or is composed of a polyester resin, the molecular weight MW of which ranges from about 1000 to about 300000. In an embodiment, the binder comprises an unsaturated polyester resin or is composed of an unsaturated polyester resin, for example, an aromatic unsaturated polyester resin or an aliphatic unsaturated polyester resin. The example of a suitable polyester-based resin includes a BPA polyester such as a BPA fumarate polyester, for example an alkoxylated (e.g., ethoxylated or propoxylated) BPA fumarate polyester.

[0119] At least some of the binder (eg, binder particles) of the functionalized fabric is present on the surface of the functionalized fabric. For example, at least some of the binder of the functionalized fabric is disposed on the surface of the fiber fabric or between fibers disposed on the surface of the fiber fabric.

[0120] In an embodiment, a majority of the binder (e.g., binder particles) of the functionalized fabric is disposed on a surface of the fiber fabric. For example, in an embodiment, at least 50% by weight (e.g., at least about 60% by weight, at least about 75% by weight, at least about 85% by weight, or at least about 90% by weight) of the binder of the functionalized fabric is disposed on one surface of the fiber fabric.

[0121] In embodiments, the binder of the functionalized fabric may be applied to the fiber fabric in the form of binder particles (which may also be described as powdered binder particles), a dispersion comprising the binder, or a solution comprising the binder.

[0122] In an embodiment, the binder of the functionalized fabric may permeate the fiber fabric.In an embodiment, the functionalized fabric may include a binder (eg, binder particles) within the fiber fabric.

[0123] Functional fabrics

[0124] The functionalized fabric of the present invention comprises a fiber fabric as described herein and a binder (eg, binder particles) as described herein.

[0125] Binder (e.g., binder particles) accounts for up to about 5% by weight of the functionalized fabric. In embodiments, the binder accounts for up to about 5.0% by weight of the functionalized fabric, such as up to about 4.5% by weight of the functionalized fabric, up to about 4.0% by weight, or up to about 3.5% by weight. In embodiments, the binder accounts for at least about 0.1% by weight of the functionalized fabric, such as at least about 0.2% by weight or at least about 0.3% by weight of the functionalized fabric. In embodiments, the binder accounts for about 0.1% to about 5.0% by weight of the functionalized fabric, such as about 0.1% to about 4.0% by weight of the functionalized fabric, or about 0.2% to about 3.5% by weight.

[0126] In embodiments, the glass fibers comprise at least about 50% by weight of the functionalized fabric, e.g., at least about 60% by weight of the functionalized fabric, at least about 70% by weight of the functionalized fabric, at least about 80% by weight of the functionalized fabric, or at least about 90% by weight of the functionalized fabric.

[0127] In an embodiment, the functionalized fabric comprises up to about 30 g / m 2 of a binder (e.g., binder particles), e.g., up to about 25 g / m 2 , up to about 20g / m 2 , up to about 18g / m 2 , up to about 16g / m 2 , up to about 15g / m 2 or up to about 13g / m 2 In an embodiment, the functionalized fabric comprises at least about 2 g / m 2 of adhesive, for example at least about 4 g / m 2 , at least about 5g / m 2 , at least about 7g / m 2 , at least about 8g / m 2 or at least about 10g / m 2 In an embodiment, the functionalized fabric comprises about 2 g / m 2 About 30g / m 2 of adhesive, for example about 4 g / m 2 About 25g / m 2 , about 4g / m2 About 15g / m 2 , about 7g / m 2 About 13g / m 2 or about 10g / m 2 About 13g / m 2 of adhesive.

[0128] In an embodiment, the functionalized fabric comprises a binder (e.g., binder particles) disposed on a surface of a fiber fabric. The fiber fabric may be described as a generally two-dimensional fabric having a top surface and a bottom surface. In an embodiment, the functionalized fabric may comprise a fiber fabric having one surface having binder particles disposed thereon and another surface substantially free of binder particles (e.g., comprising less than about 0.1 g / m 2 surface of the binder particles).

[0129] In embodiments, the functionalized fabric may include binder particles within the fiber fabric.

[0130] Functionalized fabrics include fiber fabrics and binders (e.g., binder particles), which adhere to the fiber fabrics. In an embodiment, the binder adheres to the fiber fabrics, such as the surface of the fiber fabrics. In an embodiment, the binder can be adhered to the fiber fabrics by suitable treatment (such as heating, curing or exposure to UV radiation). In an embodiment, the binder adheres to the fiber fabrics in the following manner: for example, the surface of the fiber fabrics is heated so that the binder melts or at least partially melts, such as at least partially melts on the surface of the fiber fabrics. For example, the functionalized fabrics may include solid binders (e.g., solid binder particles) that adhere to the fiber fabrics, wherein the binder (e.g., binder particles) applied to the fiber fabrics has been softened or at least partially melted previously. The inventors have found that, due to the small amount of binder (e.g., binder particles) applied to the fiber fabrics, even after the melting of the binder, discrete regions of the binder (which may be referred to as binder particles or independent binder particles) are provided in the functionalized fabrics (e.g., on the surface of the functionalized fabrics). Figure 2 3D microscopic images of examples of functionalized fabrics as described herein, it can be seen that the binder particles applied to the surface of the fiber fabric and then melted and solidified do not condense to form a layer on the surface of the fabric, but can be seen as independent binder particles. The term "independent binder particles" or "discrete binder particles" can be used herein to describe binder particles that adhere to the fiber fabric and have a particle size distribution as described herein. As described above, the terms "independent binder particles" and "discrete binder particles" are used herein to refer to the binder particles that adhere to the surface of the fiber fabric being spaced apart from each other, that is, there is a fiber fabric surface area that does not contain binder particles around each binder particle.

[0131] The present inventors have discovered that the functionalized fabrics described herein comprising a fiber fabric and about 5 wt % or less of a binder (e.g., binder particles) adhered to the fiber fabric (based on the total weight of the functionalized fabric) can be described as comprising a fiber fabric having a surface to which the binder (e.g., binder particles) is permanently adhered. The term "permanently adhered" is used herein to refer to a binder (e.g., binder particles) that cannot be removed from the fiber fabric by abrasion (e.g., abrasion testing as described in the Examples section below). The binder (e.g., binder particles) can be permanently adhered to the surface of the fiber fabric by softening or at least partially melting the binder on the surface of the fiber fabric as described herein. For example, if a microfiber fabric or Scotch-Brite is used in the absence of liquid according to ISO 11998-2006 (using an Elcometer 1720 Abrasion Tester), the binder (e.g., binder particles) can be permanently adhered to the surface of the fiber fabric. YM After scrubbing tests with the 7446 pad as the abrasive pad (weight of the abrasive pad with stand 455 g, 300 mm long scrubbing surface, 200 runs (back and forth)), no effect on the adhesive adhesion was observed and no weight loss occurred, the adhesive was considered to be permanently adhered to the surface of the fiber fabric.

[0132] In an embodiment, the functionalized fabric comprises binder particles adhered to the surface of the fiber fabric. For example, the functionalized fabric may comprise solid binder particles adhered to the fiber fabric, wherein the binder particles have previously been softened or at least partially melted on the surface of the fiber fabric.

[0133] In embodiments, the functionalized fabrics described herein may be impregnated with a resin and the resin cured to form a composite article.

[0134] In an embodiment, the functionalized fabric comprises:

[0135] Fabrics; and

[0136] Binder particles having a glass transition temperature of at most about 75°C,

[0137] The fiber fabrics include:

[0138] first fibers oriented in a first direction; and

[0139] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0140] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m 2 About 30g / m 2The binder particles adhere to the surface of the fiber fabric.

[0141] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 1 μm to about 1 mm.

[0142] In an embodiment, the functionalized fabric comprises:

[0143] Fabrics; and

[0144] Binder particles having a glass transition temperature of at most about 75°C,

[0145] The fiber fabrics include:

[0146] first fibers oriented in a first direction; and

[0147] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0148] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m 2 About 20g / m 2 The binder particles adhere to the surface of the fiber fabric.

[0149] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 1 μm to about 1 mm.

[0150] In an embodiment, the functionalized fabric comprises:

[0151] Fabrics; and

[0152] Binder particles having a glass transition temperature ranging from about 40°C to about 70°C,

[0153] The fiber fabrics include:

[0154] first fibers oriented in a first direction; and

[0155] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0156] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m2 About 20g / m 2 The binder particles adhere to the surface of the fiber fabric.

[0157] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 10 μm to about 1 mm.

[0158] In an embodiment, the functionalized fabric comprises:

[0159] Fabrics; and

[0160] Binder particles having a glass transition temperature ranging from about 40°C to about 70°C,

[0161] The fiber fabrics include:

[0162] first fibers oriented in a first direction; and

[0163] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0164] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m 2 About 20g / m 2 The binder particles adhere to the surface of the fiber fabric.

[0165] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 10 μm to about 800 μm.

[0166] In an embodiment, the functionalized fabric comprises:

[0167] Fabrics; and

[0168] Binder particles having a glass transition temperature ranging from about 40°C to about 70°C,

[0169] The fiber fabrics include:

[0170] first fibers oriented in a first direction; and

[0171] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0172] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m 2 About 20g / m 2 The binder particles adhere to the surface of the fiber fabric.

[0173] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 10 μm to about 600 μm.

[0174] In an embodiment, the functionalized fabric comprises:

[0175] Fabrics; and

[0176] Binder particles having a glass transition temperature ranging from about 40°C to about 70°C,

[0177] The fiber fabrics include:

[0178] first fibers oriented in a first direction; and

[0179] a second fiber oriented in a second direction, the first fiber comprising glass fiber and / or carbon fiber, the second fiber comprising glass fiber and / or carbon fiber, and the second direction is within 0 to 90 degrees of the first direction,

[0180] The binder particles account for about 0.1% to about 3.5% by weight of the functionalized fabric, and the functionalized fabric comprises about 2 g / m 2 About 20g / m 2 The binder particles adhere to the surface of the fiber fabric.

[0181] The binder particles attached to the functionalized fabric surface have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (based on the total number of particles) have a longest axial length ranging from about 20 μm to about 500 μm.

[0182] In an embodiment, at least about 80% by weight of the binder (e.g., binder particles) is disposed on one surface of the fiber fabric of the functionalized fabric, such as at least about 85%, at least about 90%, or at least about 95% by weight of the binder (e.g., binder particles) is disposed on one surface of the fiber fabric of the functionalized fabric. For example, the functionalized fabric may include a fiber fabric having a first surface and a second surface, the first surface having at least about 80% by weight (e.g., at least about 90% by weight or at least about 95% by weight) of the binder (e.g., binder particles) disposed thereon, and the second surface having substantially no binder (e.g., less than 5% by weight of the binder (e.g., binder particles) disposed thereon on the second surface of the fiber fabric, such as less than 3% by weight, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight of the binder (e.g., binder particles) disposed thereon on the second surface of the fiber fabric.

[0183] In an embodiment, the functionalized fabric has a surface on which at least some binder (e.g., binder particles) is present, the surface having an average gloss value of about 65 G.U. or less, such as about 60 G.U. or less. In an embodiment, the functionalized fabric has a surface on which at least some binder is present, the surface having an average gloss value ranging from about 20 G.U. to about 65 G.U., such as 25 G.U. to about 65 G.U., or about 25 G.U. to about 60 G.U.

[0184] In embodiments, the functionalized fabric comprising a binder (e.g., binder particles) has a surface having an average gloss value at least about 10 G.U. lower than the fiber fabric prior to the application of the binder, such as at least about 15 G.U. lower, at least about 20 G.U. lower, or at least about 25 G.U. lower than the fiber fabric prior to the application of the binder. When comparing the average gloss value of the surface of a functionalized fabric to the average gloss value of the surface of a fiber fabric, the same surface of the fiber fabric alone or as part of the functionalized fabric comprising a binder should be considered.

[0185] In an embodiment, the functionalized fabric comprises a unidirectional fiber fabric and a binder, the functionalized fabric having a surface on which at least some binder (e.g., binder particles) is present, the surface having an average gloss value of about 65 G.U. or less, such as about 60 G.U. or less, about 50 G.U. or less. In an embodiment, the functionalized fabric comprises a unidirectional fiber fabric and a binder, the functionalized fabric having a surface on which at least some binder is present, the surface having an average gloss value ranging from about 25 G.U. to about 65 G.U., such as about 25 G.U. to about 60 G.U. or less, or about 25 G.U. to about 50 G.U.

[0186] In an embodiment, the functionalized fabric comprises a weight per unit area greater than 1200 g / m 2 (For example, the weight per unit area range is about 1300 g / m 2 About 2500g / m 2 ) of a fiber fabric and a binder, the functionalized fabric having a surface on which at least some binder (e.g., binder particles) is present, and the average gloss value of the surface ranges from about 25 G.U. to about 60 G.U.

[0187] In an embodiment, the functionalized fabric comprises a biaxial fiber fabric and a binder, the functionalized fabric having a surface having at least some binder (e.g., binder particles) thereon, the surface having an average gloss value ranging from about 25 G.U. to about 65 G.U.

[0188] In an embodiment, the functionalized fabric comprises a weight per unit area greater than 1200 g / m 2 (For example, the weight per unit area range is about 1300 g / m 2 About 2500g / m 2 ) and a binder, and the functionalized fabric has a surface on which at least some binder (e.g., binder particles) is present, and the average gloss value of the surface ranges from about 25 G.U. to about 60 G.U.

[0189] In an embodiment, the functionalized fabric comprises a weight per unit area of ​​less than about 1300 g / m 2 (For example, the weight per unit area range is about 500g / m 2 About 1300g / m 2 ) and a binder, and the functionalized fabric has a surface on which at least some binder (e.g., binder particles) is present, and the average gloss value of the surface ranges from about 25 G.U. to about 65 G.U.

[0190] In an embodiment, the functionalized fabric comprises a weight per unit area of ​​less than about 1300 g / m 2 (For example, the weight per unit area range is about 500g / m 2 About 1300g / m 2 ) of a fiber fabric and a binder, the functionalized fabric having a surface on which at least some binder (e.g., binder particles) is present, and the average gloss value of the surface ranges from about 25 G.U. to about 65 G.U.

[0191] The average gloss value of a fabric can be determined for a surface of the fabric, such as a surface that includes at least some of the binder (e.g., binder particles) of the functionalized fabric. The gloss value can be determined using a spectrophotometer (e.g., Spectrophotometer X-Rite Ci7600), such as a spectrophotometer that allows for simultaneous measurement of a (SCE) component excluding a specular component and a (SCI) component including a specular component to provide a relative gloss value. The average gloss value can be obtained by placing the fabric on a neutral support, obtaining gloss values ​​for a plurality of (e.g., 10) points across the fabric, and providing an average gloss value. In an embodiment, the spectrophotometer (e.g., Spectrophotometer X-Rite Ci7600) can be set up with the following settings: geometry—D\8°—three beam simultaneous SCE / SCI (SPEX / SPIN); illumination—pulsed xenon lamp, calibrated D65; and aperture aperture 25 mm. The average gloss value can be provided for a sample functionalized fabric of 25 mm diameter.

[0192] Fabric Lamination

[0193] The fabric laminate comprises at least two functionalized fabric layers as described herein.

[0194] In an embodiment, the fabric laminate comprises at least two fabric layers as described herein, wherein one functionalized fabric layer is directly disposed on another functionalized fabric layer. In an embodiment, the fabric laminate comprises at least 3 functionalized fabric layers as described herein, for example at least 4, at least 6 or at least 8 functionalized fabric layers as described herein. In an embodiment, the fabric laminate comprises at most 50 functionalized fabric layers as described herein, for example at most 30, at most 25, at most 20, at most 15, at most 10 functionalized fabric layers as described herein. In an embodiment, the fabric laminate comprises 2 to 50 functionalized fabric layers as described herein, for example 4 to 30 or 6 to 25 functionalized fabric layers as described herein. In an embodiment, the fabric laminate comprises a plurality of functionalized fabric layers as described herein, wherein each layer in a plurality of functionalized fabric layers is directly disposed on another layer in a plurality of functionalized fabric layers.

[0195] In an embodiment, the fabric stack includes a plurality of functionalized fabric layers as described herein, each of the plurality of functionalized fabric layers being directly disposed on another of the plurality of functionalized fabric layers, each of the plurality of functionalized fabric layers having one surface on which a binder (e.g., binder particles) is disposed and another surface that is substantially free of binder, wherein each of the plurality of functionalized fabrics is stacked such that the surface of each of the plurality of functionalized fabrics on which the binder is disposed is directly disposed on a surface of another of the plurality of functionalized fabric layers that is substantially free of binder.

[0196] In an embodiment, the layers of the fabric laminate are adhered to each other. A fabric laminate in which the layers of the fabric laminate are adhered to each other may be referred to herein as a "consolidated fabric laminate".

[0197] In an embodiment, the layers of the fabric laminate may be adhered to each other by a suitable treatment, such as heating, curing, or exposure to UV radiation. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate so that the binder particles of the first functionalized fabric layer adhere the first functionalized fabric layer to the second functionalized fabric layer. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the glass transition temperature of the binder, such as heating to a temperature at least about 5°C higher than the glass transition temperature of the binder, heating to a temperature at least about 10°C higher than the glass transition temperature of the binder, or heating to a temperature at least about 15°C higher than the glass transition temperature of the binder. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the softening temperature of the binder, such as heating to a temperature at least about 5°C higher than the softening temperature, heating to a temperature at least about 10°C higher than the softening temperature, or heating to a temperature at least about 15°C higher than the softening temperature. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature higher than the melting temperature of the binder. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature of at least about 50°C, such as at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, or at least about 100°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature of up to about 150°C, such as up to about 130°C or up to about 120°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate to a temperature ranging from about 50°C to about 150°C, such as from about 70°C to about 130°C or from about 80°C to about 120°C. In an embodiment, the layers of the fabric laminate may be adhered to each other by heating the fabric laminate as described above for about 1 minute or more, such as up to about 1 hour, such as from about 1 minute to about 10 minutes.

[0198] In an embodiment, providing a consolidated fabric laminate may include adhering the layers of the fabric laminate to each other. In an embodiment, the layers of the fabric laminate may be adhered to each other by exposing the fabric laminate to a temperature of up to about 150° C. and a pressure below atmospheric pressure, such as a pressure in the range of about 500 mbar to about 1000 mbar, or about 600 mbar to about 1000 mbar, about 700 mbar to about 1000 mbar, about 750 mbar to about 1000 mbar, about 800 mbar to about 1000 mbar, or about 900 mbar. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of up to about 5 hours, such as up to about 3 hours, up to about 2 hours, or up to about 1 hour, to form a consolidated fabric laminate. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of at least about 10 minutes, such as at least about 30 minutes, to form a consolidated fabric laminate. In embodiments, the fabric laminate is exposed to elevated temperature (i.e., heat) and / or reduced pressure for a period of about 10 minutes to about 5 hours, e.g., about 30 minutes to about 2 hours or about 30 minutes to about 1 hour, to form a consolidated fabric laminate.

[0199] In embodiments, a fabric layup or consolidated fabric layup described herein may be impregnated with a resin and the resin cured to form a composite article.

[0200] Method for producing functionalized fabrics

[0201] Methods for producing functionalized fabrics may include:

[0202] Providing a fiber fabric as described herein;

[0203] applying binder particles having a glass transition temperature of up to about 75° C. to the fiber fabric; and adhering the binder particles to the fiber fabric to provide a functionalized fabric, wherein the binder is applied to the fiber fabric in an amount such that the binder comprises up to about 5% by weight of the functionalized fabric.

[0204] Methods for producing functionalized fabrics may include:

[0205] Providing a fiber fabric as described herein;

[0206] applying a binder (e.g., binder particles) as described herein to a fibrous fabric to provide a functionalized fabric, and

[0207] Adhere the binder particles to the fiber fabric,

[0208] wherein the binder is applied to the fiber fabric in an amount such that the binder comprises up to about 5% by weight of the functionalized fabric, and

[0209] Wherein the functionalized fabric has a surface having at least some binder present thereon, the surface having an average gloss value of about 65 G.U. or less.

[0210] In an embodiment, the method includes applying a binder (e.g., binder particles) to the fiber web to provide a binder distribution of up to about 30 g / m 2 , for example up to about 20 g / m 2 , up to about 25g / m 2 , up to about 18g / m 2 , up to about 16g / m 2 , up to about 15g / m 2 or up to about 13g / m 2 In an embodiment, the method includes applying a binder to the fiber fabric to provide a binder distribution of at least about 2 g / m 2 , for example at least about 4 g / m 2 , at least about 5g / m 2 , at least about 7g / m 2 , at least about 8g / m 2 or at least about 10g / m 2 In an embodiment, the method includes applying a binder to the fiber fabric to provide a binder distribution range of about 2 g / m 2 About 30g / m 2 , for example about 4g / m 2 About 20g / m 2 , about 4g / m 2 About 15g / m 2 , about 7g / m 2 About 13g / m 2 or about 10g / m 2 About 13g / m 2 functionalized fabrics.

[0211] In an embodiment, a binder (e.g., binder particles) is applied to a fiber fabric in an amount such that the binder accounts for up to about 5% by weight of the functionalized fabric. In an embodiment, the binder accounts for up to about 5.0% by weight of the functionalized fabric, such as up to about 4.5% by weight, up to about 4.0% by weight, or up to about 3.5% by weight of the functionalized fabric. In an embodiment, the binder accounts for at least about 0.1% by weight of the functionalized fabric, such as at least about 0.2% by weight or at least about 0.3% by weight of the functionalized fabric. In an embodiment, the binder accounts for about 0.1% to about 5.0% by weight of the functionalized fabric, such as about 0.1% to about 4.0% by weight of the functionalized fabric, or about 0.2% to about 3.5% by weight.

[0212] In an embodiment, the binder is applied to the surface of the fiber fabric, for example, by spreading binder particles over the surface of the fiber fabric.

[0213] In an embodiment, the binder is applied to the surface of the fiber fabric as binder particles. The volume average particle size of the binder particles applied to the fiber fabric may be at most about 1 mm, for example, at most about 800 μm, at most about 600 μm, at most about 500 μm, at most about 400 μm, at most about 300 μm, or at most about 200 μm. In an embodiment, the volume average particle size of the binder particles applied to the fiber fabric is greater than about 10 μm, for example, greater than about 20 μm, greater than about 30 μm, greater than about 40 μm, or greater than about 50 μm. In an embodiment, the volume average particle size range of the binder particles applied to the fiber fabric is from about 10 μm to about 1 mm, for example, from about 20 μm to about 600 μm, from about 30 μm to about 500 μm, from about 40 μm to about 400 μm, or from about 50 μm to about 300 μm. The volume average particle size of the binder particles applied to the fiber fabric can be determined using a dynamic light scattering technique on a dispersion of the binder particles prior to application to the fiber fabric. A particle size analyzer (such as available from Beckman TM The volume average particle size is determined by laser diffraction (i.e., using dynamic light scattering techniques on a dispersion of binder particles before application to the fiber fabric) using a LS13320 particle size analyzer from Sigma-Aldrich (Shanghai) in accordance with ISO 13320 2009. The sample can be analyzed twice as is after dispersion in air, and the sample amount for each test is typically about 20 g.

[0214] In an embodiment, the binder (e.g., binder particles) may be adhered to the fiber fabric by a suitable treatment such as heating, curing, or exposure to UV radiation. In an embodiment, the method comprises heating the functionalized fabric to adhere the binder to the fiber fabric. In an embodiment, the method comprises heating the binder to adhere the binder to the fiber fabric. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the glass transition temperature of the binder, for example, heating to a temperature at least about 5°C higher than the glass transition temperature of the binder, heating to a temperature at least about 10°C higher than the glass transition temperature of the binder, or heating to a temperature at least about 15°C higher than the glass transition temperature of the binder. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the softening temperature of the binder, for example, heating to a temperature at least about 5°C higher than the softening temperature, heating to a temperature at least about 10°C higher than the softening temperature, or heating to a temperature at least about 15°C higher than the softening temperature. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature higher than the melting temperature of the binder. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature of at least about 50°C, such as at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, or at least about 100°C. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature of up to about 150°C, such as up to about 130°C or up to about 120°C. In an embodiment, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric to a temperature in the range of about 50°C to about 150°C, such as about 70°C to about 130°C or about 80°C to about 120°C. In embodiments, heating the binder / functionalized fabric to adhere the binder to the fiber fabric comprises heating the functionalized fabric as described above for about 1 minute or more, such as up to about 1 hour, such as about 1 minute to about 10 minutes.

[0215] In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length of less than about 2 mm, such as less than about 1 mm, less than about 800 μm, less than about 700 μm, less than about 600 μm, or less than about 500 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length of at least about 1 μm, at least about 10 μm, or at least about 20 μm. In an embodiment, the binder particles attached to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles attached to the fiber fabric surface (by particle number) have a longest axial length in the range of about 1 μm to about 1 mm, such as in the range of about 1 μm to about 800 μm, about 10 μm to about 600 μm, or about 10 μm to about 500 μm. Binder particle size distribution can be determined as described herein.

[0216] In embodiments (e.g., where the binder of the functionalized fabric is applied to the fibrous fabric in the form of a dispersion comprising the binder or a solution comprising the binder), applying and / or adhering the binder to the fibrous fabric may include evaporating a liquid component of the binder or a solution comprising the binder.

[0217] Formed parts

[0218] The shaped component comprises a fabric laminate (eg, a consolidated fabric laminate) as described herein.

[0219] Formed parts can be produced by the following steps:

[0220] a) providing a fabric laminate as described herein;

[0221] b) shaping the fabric laminate; and

[0222] c) heating the formed laminate at a temperature of up to about 150°C.

[0223] In an embodiment, shaping the fabric layup involves placing the fabric layup (e.g., a consolidated fabric layup) on or in a mold. In an embodiment, shaping the fabric layup involves placing the fabric layup (e.g., a consolidated fabric layup) on or in a mold and applying increased heat and / or reduced pressure to the fabric layup.

[0224] In an embodiment, providing a forming component comprises forming a fabric laminate (e.g., a consolidated fabric laminate) and heating the fabric laminate (e.g., a consolidated fabric laminate) at a temperature of at least about 50°C, e.g., at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, or at least about 100°C. In an embodiment, providing a forming component comprises forming a fabric laminate (e.g., a consolidated fabric laminate) and heating the fabric laminate (e.g., a consolidated fabric laminate) at a temperature of up to about 150°C, e.g., up to about 130°C, or up to about 120°C. In an embodiment, providing a forming component comprises forming a fabric laminate (e.g., a consolidated fabric laminate) and heating the fabric laminate (e.g., a consolidated fabric laminate) at a temperature in the range of about 50°C to about 150°C, e.g., about 70°C to about 130°C, or about 80°C to about 120°C.

[0225] In an embodiment, producing a formed part may include forming a fabric laminate and heating the fabric laminate at a temperature of up to about 150° C. and a pressure below atmospheric pressure, such as a pressure in the range of about 500 mbar to about 1000 mbar, or about 600 mbar to about 1000 mbar, about 700 mbar to about 1000 mbar, about 750 mbar to about 1000 mbar, about 800 mbar to about 1000 mbar, or about 900 mbar.

[0226] In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of up to about 5 hours, e.g., up to about 3 hours, up to about 2 hours, or up to about 1 hour, to form a shaped article. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of at least about 10 minutes, e.g., at least about 30 minutes, to form a shaped article. In an embodiment, the fabric laminate is exposed to an elevated temperature (i.e., heated) and / or reduced pressure for a period of about 10 minutes to about 5 hours, e.g., about 30 minutes to about 2 hours or about 30 minutes to about 1 hour.

[0227] In embodiments, a shaped part described herein may be impregnated with a resin and the resin cured to form a composite article.

[0228] In an embodiment, the binder is selected to be compatible with the resin used to form the composite article. For example, where the functionalized fabric is to be incorporated into a composite article comprising an epoxy resin, an epoxy-compatible (e.g., epoxy-based) binder may be selected. For example, where the functionalized fabric is to be incorporated into a composite article comprising a polyester resin, a polyester-compatible (e.g., polyester-based) binder may be selected. The binder may be selected so that the binder is soluble in the resin used to form the composite article.

[0229] Functionalized fabrics described herein can be stacked in a manner that allows multiple fabric laminates to be connected / joined together. The manner of stacking functionalized fabric layers can provide different types of joints, by which multiple fabric laminates can be connected / joined together. In one example, functionalized fabric layers can be stacked directly on top of each other (i.e., the edges of each functionalized fabric layer are directly located on top of each other), and two or more fabric laminates (e.g., consolidated fabric laminates) are joined together so that the edge of one fabric laminate abuts the edge of the second fabric laminate (butt joint). In another example, functionalized fabric layers can be stacked so that at least one functionalized fabric layer (at least two or at least three functionalized fabric layers in some examples) overlaps one or each lower layer of the functionalized fabric, and the two fabric laminates formed in this way can then be joined by a lap joint. In another example, multiple functionalized fabric layers can be stacked to form holes (mortises) in the joint edges of the fabric laminates, and the jointed fabric laminates including multiple functionalized fabric layers are stacked to form protrusions (tenons) in the joint edges of the fabric laminates, so that the protrusions of one fabric laminate fit into the holes of another fabric laminate (mortise and tenon joints).

[0230] The tongue-and-groove connection described herein may be considered similar to the tongue-and-groove type joints commonly used in carpentry and construction. The concept involves forming a protruding tongue on one fabric laminate (e.g., a consolidated fabric laminate) and forming a corresponding groove or slot on another fabric laminate (e.g., a consolidated fabric laminate). When assembling (i.e., connecting / joining) two (or more) fabric laminates, the tongue fits tightly into the groove, thereby forming a strong and secure joint that resists torsional and tensile forces. It has been found that the use of such a tongue-and-groove connection between fabric laminates reduces slippage of the fabric laminates during assembly, which in turn also reduces wrinkling in the resulting composite article, thereby providing improvements in the assembly of composite articles formed from fabric laminates (including consolidated fabric laminates and formed parts).

[0231] In an embodiment, the fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part) comprises a plurality of functionalized fabric layers as described herein, wherein the plurality of functionalized fabric layers are stacked such that at least one edge of the fabric laminate forms a groove configuration (concave) or a tongue configuration (convex).

[0232] In an embodiment, a fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part) comprises a plurality of functionalized fabric layers as described herein, wherein the plurality of functionalized fabric layers are stacked such that one edge of the fabric laminate forms a groove configuration (concave shape) and the opposite edge of the fabric laminate forms a tongue configuration (convex shape). Figure 3a and Figure 3bA cross section of a fabric stack is shown where multiple functionalized fabric layers are stacked such that one edge of the fabric stack forms a groove "G" configuration (concave) and the opposing edge of the fabric stack forms a tongue "T" configuration (convex).

[0233] In an embodiment, a kit of parts is provided, the kit of parts comprising:

[0234] A fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part) comprising a plurality of functionalized fabric layers as described herein, wherein the plurality of functionalized fabric layers are stacked such that at least one edge of the fabric laminate forms a groove configuration (concave shape); and

[0235] a fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part) comprising a plurality of functionalized fabric layers as described herein, wherein the plurality of functionalized fabric layers are stacked such that at least one edge of the fabric laminate forms a tongue configuration (convex shape),

[0236] Wherein the tongue configuration is configured to fit into the groove configuration.

[0237] The fabric stack (the fabric stack may be a consolidated fabric stack or formed into a shaped part as described herein) comprises a plurality of functionalized fabric layers as described herein. The fabric stack (the fabric stack may be a consolidated fabric stack or formed into a shaped part as described herein) is formed of at least 3 functionalized fabric layers, the fabric stack comprising stacked layers such that at least one edge of the fabric stack forms a groove configuration (concave) or a tongue configuration (convex). The fabric stack (the fabric stack may be a consolidated fabric stack or formed into a shaped part as described herein) may be considered to be formed of at least one functionalized fabric top layer, at least one functionalized fabric middle layer and at least one functionalized fabric bottom layer, the fabric stack comprising stacked layers such that at least one edge of the fabric stack forms a groove configuration (concave) or a tongue configuration (convex). In an embodiment, a fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part as described herein) may be considered to be formed from at least one functionalized fabric top layer, a plurality of functionalized fabric middle layers, and at least one functionalized fabric bottom layer, the fabric laminate comprising stacked layers such that at least one edge of the fabric laminate forms a groove configuration (concave) or a tongue configuration (convex). In an embodiment, a fabric laminate (the fabric laminate may be a consolidated fabric laminate or formed into a shaped part as described herein) may be considered to be formed from a plurality of functionalized fabric top layers, a plurality of functionalized fabric middle layers, and a plurality of functionalized fabric bottom layers, the fabric laminate comprising stacked layers such that at least one edge of the fabric laminate forms a groove configuration (concave) or a tongue configuration (convex). A "groove configuration" comprises a recessed portion formed along one edge of the fabric laminate, the recessed portion or recessed portion being formed by the position of at least one middle layer of functionalized fabric or multiple middle layers of functionalized fabric. In Figure 3a and Figure 3b An example of a groove configuration can be seen in FIG, which is labeled "G". In an embodiment, a "groove configuration" can be a stepped groove configuration formed by multiple intermediate layers of a fabric laminate. Figure 3b An example of a stepped groove configuration can be seen in the Figure 1, where the stepped groove configuration is labeled "G". A "tongue configuration" includes a protrusion formed along one edge of the fabric laminate, the protrusion being formed by the position of at least one intermediate layer of the functionalized fabric or multiple intermediate layers of the functionalized fabric. Figure 3a and Figure 3b An example of a tongue configuration can be seen in , which is labeled "T". In an embodiment, the "tongue configuration" can be a stepped tongue configuration formed by multiple intermediate layers of a fabric laminate. Figure 3b An example of a stepped tongue configuration can be seen in , where the stepped groove configuration is labeled “T”.

[0238] In an embodiment, the groove (a recessed portion formed by the position of at least one intermediate layer of the functionalized fabric of the fabric stack or the formed part) is composed of at least two functionalized fabric layers as defined herein, for example at least three functionalized fabric layers, at least four functionalized fabric layers, or five or more functionalized fabric layers as defined herein.

[0239] In an embodiment, the tongue (a protrusion formed by the position of at least one intermediate layer of a functionalized fabric of a fabric stack or a forming part) is composed of at least two functionalized fabric layers as defined herein, for example at least three functionalized fabric layers as defined herein, at least four functionalized fabric layers, or five or more functionalized fabric layers as defined herein.

[0240] In an embodiment, the middle layer of the functionalized fabric of the fabric laminate (the functionalized fabric layer of the fabric laminate positioned to form the tongue and / or groove configuration of the fabric laminate) is formed by at least two functionalized fabric layers, for example, at least three functionalized fabric layers as defined herein, at least four functionalized fabric layers, or five or more functionalized fabric layers as defined herein. In an embodiment, the middle layer of the functionalized fabric of the fabric laminate is formed by 2 to 10 functionalized fabric layers.

[0241] In an embodiment, the top layer of the functionalized fabric of the fabric stack is formed by at least two functionalized fabric layers, for example, at least three functionalized fabric layers as defined herein, at least four functionalized fabric layers, or five or more functionalized fabric layers as defined herein. In an embodiment, the top layer of the functionalized fabric of the fabric stack is formed by 2 to 5 functionalized fabric layers.

[0242] In an embodiment, the bottom layer of the functionalized fabric of the fabric stack is formed by at least two functionalized fabric layers, for example, at least three functionalized fabric layers as defined herein, at least four functionalized fabric layers, or five or more functionalized fabric layers as defined herein. In an embodiment, the bottom layer of the functionalized fabric of the fabric stack is formed by 2 to 5 functionalized fabric layers.

[0243] Also described herein is a method of forming a subcomponent article (e.g., a subcomponent for a wind turbine blade) comprising a fabric layup or a shaped component, the method comprising the steps of:

[0244] providing a plurality of functionalized fabric layers as described herein; and

[0245] A plurality of functionalized fabric layers are stacked to form a first fabric laminate edge having a groove configuration and a second fabric edge having a tongue configuration, wherein the second fabric laminate edge is opposite the first fabric laminate edge.

[0246] Also described herein is a method for joining at least two fabric layups or formed parts as described herein, the method comprising:

[0247] Providing a first fabric laminate as described herein and a second fabric laminate as described herein, the first fabric laminate having a laminate edge in a groove configuration and the second fabric laminate having a laminate edge in a tongue configuration; and

[0248] The first and second fabric layups are positioned adjacent to each other in a mold such that the tongues of the second fabric layup are inserted into the grooves of the first fabric layup.

[0249] Example

[0250] The following are examples of fabrics and related aspects described herein. Therefore, these examples should not be considered as limiting the present disclosure, but are only used to teach how to implement the methods of the present disclosure and obtain the products of the present disclosure.

[0251] Functionalized fabrics were produced by applying different amounts of binder to one surface of different fiber fabrics. The materials used are described below, and Table 1 summarizes each functionalized fabric of the Examples.

[0252] Fiber fabrics used in the examples

[0253] All fiber fabrics used in the examples are non-crimp fabrics and contain glass first fibers and glass second fibers, the first fibers and the second fibers being held in their respective orientations by stitching yarns. The glass fibers constituting the fiber fabrics contain an epoxy resin compatible sizing agent.

[0254] The unidirectional fiber fabrics used in these embodiments (indicated as "UD" in the table below) contain up to about 5% by weight of the second fibers (glass fibers) of the fiber fabric, and at least 95% by weight of the first fibers (glass fibers) of the fiber fabric, and the second direction is substantially perpendicular to the first direction. The unidirectional fabrics are referred to as "UD0" and "UD90", and the UD0 fabric contains the first fibers oriented in the 0 direction (i.e., aligned with the length of the fabric), and the UD90 fabric contains the first fibers oriented in the 90 direction (i.e., perpendicular to the length of the fabric).

[0255] The biaxial fiber fabrics used in these examples contain at least about 15% by weight of the fiber fabric of second fibers (glass fibers), and the second direction is substantially perpendicular to the first direction (these fabrics are designated as "BX90" in the table below) or at about 45 degrees to the first direction (these fabrics are designated as "BX45" in the table below).

[0256] The inventors contemplate that other fiber fabrics described herein may provide functionalized fabrics that provide similar advantages as the fiber fabrics used in these examples.

[0257] Measurement method

[0258] The glass transition temperature of the binder was determined using differential scanning calorimetry (DSC) according to EN ISO 11357-2 (determination of the glass transition temperature) by heating the binder at a heating rate of 10 K / min from -60°C to 120°C at an air flow rate of 80 mL / min, then holding at 120°C for 5 minutes, then cooling from 120°C to -60°C at a cooling rate of 10 K / min, then holding at -60°C for 5 minutes, then heating again from -60°C to 120°C at a heating rate of 10 K / min. The glass transition temperature was determined as the value provided by the second heating cycle.

[0259] The volume average particle size of the binder applied to the fiber fabrics described in the following examples to provide the functionalized fabrics was determined as follows: using a particle size analyzer (obtained from Beckman TM The dispersion of the binder was analyzed using a dynamic light scattering technique using an LS13320 particle size analyzer (Diesel), and the dispersion of the binder was analyzed using a dynamic light scattering technique according to the ISO 133202009 standard.

[0260] The shear modulus G of the adhesive used in the following examples at 30°C was determined using an oscillatory rheometer at 0.1% deformation and a frequency of 1 Hz in a plane-to-plane geometry using an adhesive sample having a thickness of 400 μm and a diameter of 25 mm, using a heating-cooling-heating cycle of heating from 30°C to 130°C at a heating rate of 3°C / min, cooling from 130°C to 30°C and heating from 30°C to 130°C at a heating rate of 3°C / min.

[0261] The dynamic viscosity η of the adhesive used in the following examples at 130°C was determined using an oscillatory rheometer at 0.1% deformation and a frequency of 1 Hz in a plane-plane geometry using an adhesive sample having a thickness of 400 μm and a diameter of 25 mm, using a heating-cooling-heating cycle, which is heated from 30°C to 130°C at a heating rate of 3°C / min, cooled from 130°C to 30°C and heated from 30°C to 130°C at a heating rate of 3°C / min.

[0262] Binder

[0263] EP1-Purchased from Hexion TMThe epoxy resin has a glass transition temperature of 58°C (determined using DSC as described above), a softening point of 72°C (determined using an oscillatory rheometer according to the method described above), and a volume average particle size of about 80 μm (determined by using a particle size analyzer (obtained from Beckman TM LS13320) determined using dynamic light scattering, see also Figure 1 , line A), the shear modulus G at 30°C is 11.5 MPa (determined using an oscillatory rheometer as described above), the dynamic viscosity η at 130°C is 32.5 Pa.s (determined using an oscillatory rheometer as described above), the molecular weight Mw is 5245, and the polydispersity is 2.83 (determined as Mw / Mn).

[0264] EP2-purchased from CTP TM The epoxy-based binder has a glass transition temperature of 54°C (determined using DSC as described above), a softening point of 69°C (determined using an oscillatory rheometer according to the method described above), and a volume average particle size of about 169 μm (determined using DSC as described above, see also Figure 1 , line B), the shear modulus G at 30°C is 18.4 MPa (determined using an oscillatory rheometer as described above), the dynamic viscosity η at 130°C is 16.8 Pa.s (determined using an oscillatory rheometer as described above), the molecular weight Mw is 4771, and the polydispersity is 2.83 (determined as Mw / Mn).

[0265] Polyester adhesive - purchased from Coim TM The polyester-based binder particles have a glass transition temperature of 46° C. (determined using DSC as described above), a softening point of 57° C. (determined using an oscillatory rheometer according to the method described above), and a volume average particle size of about 185 μm (determined by using a particle size analyzer (obtained from Beckman TM LS13320) determined using dynamic light scattering, see also Figure 1 , line C), the shear modulus G at 30°C is 30.7 MPa (determined using an oscillatory rheometer as described above), the dynamic viscosity η at 130°C is 387 Pa.s (determined using an oscillatory rheometer as described above), the molecular weight Mw is 185710, and the polydispersity is 28.87 (determined as Mw / Mn).

[0266] Table 1

[0267]

[0268] The functionalized fabrics of Examples 1 to 12 were provided in the following manner: the resin binder in the amount shown in Table 1 was applied to the above fiber fabric, and after the resin binder was applied to the fiber fabric, it was heated to a temperature of 110° C. (a temperature higher than the melting temperature of each resin binder) for 1 minute, and then cooled to room temperature to adhere the binder particles to the surface of the fiber fabric. Figure 2 An example of an image (taken using a 3D microscope) of the surface of a functionalized fabric as described herein is shown, in which a binder has been attached to the surface of the fiber fabric by melting and solidifying (by cooling) the binder. Figure 2 As can be seen in FIG. 1 , the functionalized fabric comprises binder particles (discrete binder particles) adhered to the surface of the fiber fabric, and the binder particles are spaced apart from each other, i.e., there is a fiber fabric surface area without binder particles around each binder particle.

[0269] Figure 4a An example of an image (taken using a 3D microscope) of the surface of a functionalized fabric produced according to Example 1 is shown. Figure 4b It is shown Figure 4a The particle size distribution of the binder on the surface of the functionalized fabric is shown in the figure. YM Optical microscope) and related image analysis software (ImageJ software) to calculate the 5 mm 2 The binder particle size distribution over the area is determined to thereby determine the binder particle size distribution showing the range of the longest axial length of each adhered binder particle.

[0270] Figure 5a An example of an image (taken using a 3D microscope) of the surface of a functionalized fabric produced according to Example 10 is shown. Figure 5b It is shown Figure 5a The particle size distribution of the binder on the surface of the functionalized fabric is shown in the figure. TM Optical microscope) and related image analysis software (ImageJ software) to calculate the 10 mm 2 The binder particle size distribution over the area is determined to thereby determine the binder particle size distribution showing the range of the longest axial length of each adhered binder particle.

[0271] Wear test

[0272] The adhesion strength between the fiber fabric and the adhered binder particles of the functionalized fabric of Example 11 was determined using a scrub test (Elcometer 1720 Abrasion Tester) in accordance with ISO 11998-2006. The test was conducted without liquid using three abrasives: microfiber fabric, Scotch-BriteTM Type 7446 pad and sandpaper grade 100. Weight of the abrasive pad with stand is 455 g. Scrubbing surface is 300 mm. 200 runs (back and forth) are performed. For each functionalized fabric tested, the following results are obtained:

[0273] Scrub Test Using Microfiber Fabric - No effect on adhesive adhesion and no weight loss. Slight visual changes were noted where the fabric was abraded.

[0274] Using Scotch-Brite TM Scrub Test with Type 7446 Pad - No effect on adhesive adhesion and no weight loss. Slight visual changes were noted where the fabric was worn.

[0275] Scrub test using sandpaper P100 – the fabric was destroyed. After only 5 to 10 runs, fuzz began to appear. The binder was found to remain within the fuzz glass. This indicates that the adhesion between the adhered binder particles and the fiber fabric was greater than the abrasion resistance of the fiber fabric.

[0276] Thus, after these tests, the inventors have discovered that the binder particles adhered to the fiber fabrics of these functionalized fabrics are permanently adhered to the surface of the fiber fabrics in that the binder particles cannot be removed from the fiber fabrics by abrasion as described above.

[0277] The inventors contemplate that other functionalized fabrics described herein will exhibit similar abrasion resistance.

[0278] The functionalized fabric of each example was found to be extremely well handled without shedding of the binder.

[0279] The functionalized fabrics were then formed into a fabric laminate by stacking 5 to 20 layers, and each of the functionalized fabrics of Examples 1 to 12 formed a different fabric laminate.

[0280] Each type of fabric layup was then shaped using a mould and heated under reduced pressure of about 900 mbar for a period of about 30 minutes to 1 hour. It was found that at temperatures in the range of 50°C to 100°C, each fabric layup was successfully consolidated to form a shaped part (i.e., a part that remained in the form of the mould even after being removed from the mould) within this relatively short period of time, with a temperature of about 100°C providing the most sharply defined shaped part.

[0281] Then, epoxy resin or polyester resin was injected into each shaped part formed by different functionalized fabrics. Epoxy resin was injected into the shaped part containing the functionalized fabric containing epoxy binder, and polyester resin was injected into the shaped part containing the functionalized fabric containing polyester binder. Epoxy / polyester resin was also injected into the sample of each fiber fabric used in Examples 1 to 12 to which the binder had not been applied for comparison (Reference Examples 1 to 12, respectively). The resin-injected shaped part was cured to form a composite product.

[0282] It was found that shaped parts formed from the functionalized fabrics of Examples 1 to 12 exhibited excellent infusion rates, and in fact exhibited faster infusion rates than corresponding fiber fabrics without a binder.

[0283] The mechanical properties (e.g., shear and strength properties in the 0° (first direction), 45°, and 90° directions) of composite articles comprising the functionalized fabrics of Examples 1 to 12 were found to be comparable to those of composite articles comprising corresponding fiber fabrics without a binder.

[0284] Gloss measurement

[0285] Gloss measurements were performed on a number of functionalized fabrics produced according to the Examples and Reference Examples. Gloss measurements were performed using a spectrophotometer X-Rite Ci7600 device using the following settings:

[0286] Geometry: D\8° - Three beams simultaneous SCE / SCI (SPEX / SPIN)

[0287] Lighting: Pulsed Xenon lamp, calibrated D65

[0288] Aperture: 25mm.

[0289] The spectrophotometer device contains two ports, a sample viewing port and a specular reflectance port. The viewing port contains a receiver and a photosensitive detector that quantifies the light reflected from the sample surface. The specular reflectance port can be opened or closed to control the type of measurement. If the port is open, the device will take a specular excluded (SPEX) reading to provide a specular excluded (SCE) value for the gloss measurement. If the port is closed, the device will take a specular included (SPIN) reading to provide a specular included (SCI) component for the gloss measurement. The ability to measure SCI / SCE simultaneously allows for the calculation of a relevant gloss value related to the appearance of the product.

[0290] The gloss measurement of each test sample is provided in the following manner: the functionalized fabric sample or the reference fabric sample is placed on a neutral support (e.g., cardboard with double-sided tape to avoid wrinkling and keep the glass rovings aligned) with the surface to which the binder resin is adhered facing away from the support (i.e., towards the aperture of the spectrophotometer). The sample is then clamped between the aperture and the sample holder. The sample is oriented so that the rovings constituting the warp of the fabric are oriented vertically. Even for fabrics with a warp orientation of 90° compared to the roll length, the warp is placed in a vertical orientation. For each sample, 10 random points on a 25 mm diameter area were studied, two measurements were made at each point and the average of these values ​​is provided. The results are provided in Table 2 below.

[0291] Table 2

[0292] Functionalized fabric of the embodiment Average gloss (GU) 1 51.9 2 53.6 3 40.0 4 63.3 5 41.3 11 46.0 Reference Examples 1 to 3 76.3 Reference Example 4 88.3 Reference Example 5 79.2 Reference Example 11 79.0

[0293] The results provided above show that the functionalized fabrics of the examples exhibit lower average gloss values ​​compared to the reference fabrics. Without being bound by theory, the lower average gloss values ​​are believed to be due to the lower amount of binder employed in these functionalized fabrics, resulting in discrete binder regions (e.g., independent binder particles) on the surface of the functionalized fabrics (e.g., rather than a continuous binder layer on the fabric surface).

[0294] The inventors also prepared and tested functionalized fabrics similar to those described above, but without using a series of other fiber fabrics described herein to provide the functionalized fabrics. These additional functionalized fabrics were found to provide similar advantages to the fiber fabrics employed in these examples.

[0295] In addition, the inventors have discovered that the fabric layups or formed parts described herein can be used to significantly improve the layup speed of a composite article comprising the formed parts described herein. For example, formed parts comprising the functionalized fabrics described herein can be employed during the manufacture of wind turbine blades by incorporating the formed parts directly into the wind turbine blades during the layup process.

[0296] Assembling functionalized fabrics to form sub-component articles, such as sub-components of wind turbine blades

[0297] Two or more fabric layups or formed components as described above may be assembled to form a subcomponent article, such as a subcomponent of a wind turbine blade.

[0298] The inventors have discovered that advantages may be provided by providing a fabric laminate comprising a plurality of functionalized fabric layers as described herein (the fabric laminate may be a consolidated fabric laminate or formed as a shaped part), wherein the plurality of functionalized fabric layers are stacked such that one edge of the fabric laminate forms a groove configuration (concave) and the opposite edge of the fabric laminate forms a tongue configuration (convex). Figure 3a and Figure 3b A cross section of a fabric laminate is shown where multiple functionalized fabric layers are stacked such that one edge of the fabric laminate forms a groove "G" configuration (concave) and the opposite edge of the fabric laminate forms a tongue "T" configuration (convex). The inventors have discovered that by providing a fabric laminate with such a tongue-and-groove configuration, so that adjacent fabric laminates can be nested into one another, the assembly and mechanical properties of the resulting sub-assembly article are improved.

[0299] The inventors have found that the tongue and groove arrangement solves problems encountered during layup (compared to, for example, laying up a fabric layup that has been stacked so that the fabric layers are aligned or overlapped on top of each other to form a stepped configuration at opposing edges, for example by assembling using butt joints or lap joints as described above), such as fabric layup slippage and / or fabric layup wrinkling.

[0300] The inventors have also discovered that the tongue and groove arrangement described herein also improves the mechanical strength of composite articles, including subcomponent articles, by reducing the size of "resin gaps" (i.e., gaps between fabric plies that are filled with resin during formation of the composite article due to gaps formed between adjacent fabric plies).

[0301] Thus, the present inventors have surprisingly found that a fabric layup having a tongue and groove configuration can be used to provide a subcomponent for a wind turbine blade having improved properties, such as improved mechanical uniformity.

[0302] The features disclosed in the foregoing description or in the following claims or in the accompanying drawings, expressed in their specific form or in terms of means for performing the disclosed functions or methods or processes for obtaining the disclosed results, may, where appropriate, be used alone or in any combination of these features to realize the invention in its various different forms.

[0303] Although the present invention has been described in conjunction with the above exemplary embodiments, many equivalent modifications and variations will be apparent to those skilled in the art when this disclosure is given. Therefore, the exemplary embodiments of the present invention set forth above are considered to be illustrative rather than restrictive. Various changes may be made to the described embodiments without departing from the spirit and scope of the present invention.

[0304] For the avoidance of any doubt, any theoretical explanations provided herein are intended to enhance the reader's understanding. The inventors do not wish to be bound by any of these theoretical explanations.

[0305] Any section headings used herein are for organizational purposes only and are not to be construed as limiting the subject matter described.

[0306] If a standard test is referred to herein, the version of the test referred to is the most recent version at the time this patent application was filed, unless otherwise stated.

[0307] Throughout this specification, including the claims that follow, unless the context requires otherwise, the words "comprise" and "comprising" and variations such as "have" and "containing", will be understood to imply the inclusion of stated integers or steps or groups of integers or steps but not the exclusion of any other integers or steps or groups of integers or steps.

[0308] It must be noted that, as used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural referents unless the context clearly indicates otherwise. Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about", it should be understood that the particular value forms another embodiment. The term "about" in relation to a numerical value is optional and means, for example, + / - 10%.

Claims

1. A functionalized fabric comprising: Fabrics; and Binder particles having a glass transition temperature of at most about 75°C, The fiber fabric comprises: first fibers oriented in a first direction; and second fibers oriented in a second direction, the first fibers comprising glass fibers and / or carbon fibers, the second fibers comprising glass fibers and / or carbon fibers, and the second direction being within 0 to 90 degrees of the first direction, The binder particles comprise up to about 5% by weight of the functionalized fabric, and the binder particles are adhered to the surface of the fiber fabric.

2. The functionalized fabric of claim 1, wherein the binder particles comprise from about 0.1 wt% to about 3.5 wt% of the functionalized fabric.

3. The functionalized fabric according to claim 1 or claim 2, comprising about 2 g / m 2 About 20g / m 2 of the binder particles.

4. A functionalized fabric according to any one of the preceding claims, wherein the binder particles adhered to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles adhered to the surface of the fiber fabric, based on the total number of particles, have a longest axial length of less than about 1 mm.

5. The functionalized fabric according to any one of the preceding claims, wherein the binder particles adhered to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles adhered to the surface of the fiber fabric, based on the total number of particles, have a longest axial length ranging from about 1 μm to about 1 mm.

6. The functionalized fabric of any of the preceding claims, wherein the functionalized fabric has a surface having a binder thereon, the surface having an average gloss value of about 65 G.U or less.

7. The functionalized fabric of claim 6, wherein the functionalized fabric has a surface having a binder thereon, the surface having an average gloss value ranging from about 25 G.U. to about 60 G.U.

8. The functionalized fabric according to any one of the preceding claims, wherein the fiber fabric is a unidirectional fiber fabric or a multi-axial fiber fabric.

9. The functionalized fabric according to any one of the preceding claims, having a weight per unit area in the range of about 500 g / m 2 About 2500g / m 2 .

10. The functionalized fabric of any one of the preceding claims, wherein the binder particles comprise a thermoplastic binder.

11. The functionalized fabric of any one of the preceding claims, wherein the binder particles have a glass transition temperature in the range of about 40°C to about 70°C, or about 40°C to about 60°C.

12. A functionalized fabric according to any one of the preceding claims, wherein the binder comprises epoxy, acrylate or ester functional groups.

13. The functionalized textile according to any one of the preceding claims, wherein at least the first fibers or the second fibers are glass fibers, optionally wherein both the first fibers and the second fibers are glass fibers.

14. The functionalized fabric according to any one of the preceding claims, wherein the fiber fabric is a non-crimp fabric and the functionalized fabric comprises stitching yarns, wherein the stitching yarns hold the first fibers and the second fibers in their respective orientations.

15. The functionalized fabric of any one of the preceding claims, wherein at least about 80% by weight of the binder particles are disposed on one surface of the fiber web of the functionalized fabric.

16. A textile laminate comprising at least two functionalized textile layers according to any one of claims 1 to 15, wherein one functionalized textile layer according to any one of claims 1 to 15 is directly arranged on the other functionalized textile layer according to any one of claims 1 to 15.

17. A shaped part comprising a fabric layup according to claim 16.

18. A method for producing a functionalized fabric, the method comprising: Providing a fiber fabric, the fiber fabric comprising first fibers oriented in a first direction and second fibers oriented in a second direction, the first fibers comprising glass fibers and / or carbon fibers, the second fibers comprising glass fibers and / or carbon fibers, and the second direction being within 0 to 90 degrees of the first direction; applying binder particles having a glass transition temperature of at most about 75° C. to the fiber fabric; and adhering the binder particles to the fiber fabric to provide the functionalized fabric, wherein the binder is applied to the fiber fabric in an amount such that the binder comprises at most about 5% by weight of the functionalized fabric.

19. The method for producing a functionalized fabric according to claim 18, wherein adhering the binder to the fiber fabric comprises heating the functionalized fabric.

20. The method for producing a functionalized fabric according to claim 18 or 19, wherein the binder particles are applied to the fiber fabric and adhered to the fiber fabric so that the binder particles adhered to the surface of the functionalized fabric have a particle size distribution such that at least 90% of the binder particles adhered to the surface of the fiber fabric, based on the total number of particles, have a longest axial length ranging from about 1 μm to about 1 mm.

21. The method for producing a functionalized fabric according to claim 20, wherein the volume average particle size of the binder particles applied to the fiber fabric ranges from about 20 μm to about 600 μm.

22. A method for producing a functionalized fabric according to any one of claims 18 to 21, wherein the functionalized fabric has a surface on which at least some of the binder is present, the surface having an average gloss value of about 65 G.U. or less.

23. A method for producing a shaped part, the method comprising: stacking a plurality of functionalized fabric layers according to any one of claims 1 to 15 to provide a fabric laminate; shaping the fabric laminate; as well as The fabric laminate is heated at a temperature of up to about 150°C.

24. The method of claim 23, comprising heating the fabric layup at a temperature of up to about 150°C and a pressure ranging from about 750 mbar to atmospheric pressure.